Violation of the Right to Decent Work for Persons with Disabilities - Kemal Firmanda; Balu Tethuka; Azka Putri Nur Aini; Puput Rizky Aulia; Rizqi Purnama Trian Saputra; Muhammad Fadil; Muhammad Farid Wajdi; Yusril Mahendra (Universitas Negeri Surabaya, 2025)
Equal rights for individuals with disabilities. This research investigates different sign language training centers, accommodation options, and assistive devices for disabilities, focusing on accessibility for individuals with disabilities. The study's findings show that there are insufficient advancements in accessibility, with numerous obstacles still encountered by individuals with disabilities. These obstacles consist of insufficient disability-accessible facilities, scarcity of readily available information, and low awareness among the community and policymakers about the unique requirements of individuals with disabilities. This research indicates that enhanced regulation and oversight are necessary, alongside the active involvement of all stakeholders, to achieve inclusive and accessible facilities for individuals with disabilities. It is therefore anticipated that individuals with disabilities will be able to fully exercise their rights and engage in community life without facing discrimination.